NEW NUMBER NUSSELT CORRELATION FOR THE ANNULAR SPACE OF THE TUBE IN TUBE HEAT EXCHANGER - Maria Popa (Romanian Journal of Petroleum & Gas Technology)
The use of Nusselt number correlation in the annular space of a tube-in-tube heat exchanger is a difficult task for researchers, since this correlation is deduced specifically for certain geometrical features. As such, researchers would usually only present limited areas of applicability. This paper presents the algorithm for establishing a new Nusselt number correlation for the annular space of a tube-in-tube heat exchanger with warm water flowing inside in counterflow with cold water in the annular space. The objective of the research was to establish the Nusselt number that allows the calculation of the partial convective heat transfer coefficient on the cold fluid side for a laminar flow regime. This correlation must be of the form: Nu = C·Rem·Prn. This was possible by processing the experimental data by applying the least squares method, as an optimization method. Five sets of experimental data were used for this study. A steel tube in tube heat exchanger was used for this work.